Diversity of Edaphic Organisms in Natural Field and Olericulture in Dom Pedrito, Municipality Located in the Pampa Biome - G. da S. Nascimento, Shirley (2022)
The edaphic organisms that live in the soil have several fundamental roles in the planet's ecosystem, some are responsible for the decomposition of organic matter, provide nutrients for plant growth, improve soil productivity, and help to control undesirable organisms in it. The objective of this work was to compare the diversity of soil fauna in agricultural properties in the municipality of Dom Pedrito, which is located in the state of Rio Grande do Sul. The study was conducted in two rural properties in the municipality, with rangelands and vegetable production. The collection of edaphic organisms took place in January (summer) of the year 2020. For the capture of invertebrates, PROVID-totaling 20 traps in each area. After seven days, the traps were removed, taken to the laboratory and later forwarded for identification. The edaphic fauna was evaluated quantitatively through the abundance of orders, and qualitatively through the Simpson Dominance Index (D). The parameters evaluated for the population of the edaphic fauna were wealth: abundance, Simpson and Shannon diversity index. The taxonomic groups found were: i) Arachnid (mites, spiders, harvestmen and scorpions); ii) Hymenoptera; iii) Hemiptera; iv) Homoptera, v) Collembola; vi) Crustaceae e; vii) Demáptera.Â